Penatalaksanaan Fisioterapi Pada Penderita Pneumonia Di Rs Paru Dr. Ario Wirawan Salatiga - Indriyani, Indriyani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Pneumonia is an inflammation (inflammation) in the lungs (alveoli) that can be caused due to microorganisms and non microorganisms. The presence of tightness, chest pain, decreased thoracic expansion, and pectoralis major muscle spasms and upper trapezius is a physiotherapy problem that we can provide interventions such as Infra Red (IR), Breathing Exercise, and Thoracic Expansion Exercise. To determine the benefits of physiotherapy management with IR (Infra Red) modalities, Breathing Exercise, and Thoracic Expansion Exercise on Pneumonia against stiffness, pain, chest, and decreased thoracic expansion. The development with appropriate therapy was the change of pain with VAS scale from 4,3 to 1,1, then after three therapeutics there is an increase in thoracic expansion of 1 cm, and the decrease of spasm in the auxiliary muscles. IR (Infra Red), Breathing Exercise, and Thoracic Expansion Exercise can reduce pain, spasm, increase thoracic expansion.